A nonsurgical treatment of peri‐implantitis using mechanic, antiseptic and anti‐inflammatory treatment: 1 year follow‐up - Yaniv Mayer; Ofir Ginesin; Jacob Horwitz (Wiley, 2020)
Abstract Aims The study's aim was to assess the clinical outcome 6 and 12 months after a nonsurgical treatment of peri‐implantitis per se or in conjunction with a combination of local antiseptic and anti‐inflammatory treatment. Materials and methods Included were 69 patients with periodontitis, with 106 implants, diagnosed with peri‐implantitis. Peri‐implantitis was defined as radiographic bone loss ≥3 mm, probing depth (PD) ≥ 6 mm, with bleeding on probing. Group M peri‐implantitis was treated with ultrasonic debridement and soft tissue curettage. Group P had additional implant surface treatment with rotatory hand piece composed of chitosan bristle, soft tissue curettage combined with application of 0.95% hypochlorite and 1 mg minocycline HCl. Results After 6 months, both groups demonstrated significant reduction of mean plaque index, PD, and clinical attachment level (0.71 ± 0.57, 0.81 ± 0.55; 4.77 ± 0.73 mm, 4.42 ± 0.5 mm; 5.03 ± 0.86 mm, 5.13 ± 0.73 mm; respectively) and bleeding on probing. After 6 and 12 months, group P showed significantly better PD results compared to group M. The bleeding was significantly less in group P after 12 months (15.3% ± 6.2, 25.1% ± 8.2, respectively). Conclusions Adjunctive treatment with local antiseptic and anti‐inflammatories during mechanical phase was positively associated with inflammation reduction and connective tissue reattachment.